2014
DOI: 10.1590/s0102-67202014000300006
|View full text |Cite
|
Sign up to set email alerts
|

Importance of biopsies and histological evaluation in patients with chronic diarrhea and normal colonoscopies

Abstract: BackgroundIn patients with chronic diarrhea, colonoscopy may identify inflammatory causes or some occult disease, and also can show a normal mucosa. Serial biopsies of intestinal mucosa can be useful for a differential diagnosis, and to modify the treatment.AimTo evaluate whether the biopsies performed in patients with chronic diarrhea and a normal colonoscopy contribute to the differential diagnosis and alter the therapeutic approach.MethodsA descriptive, retrospective and cross-sectional study using a comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 19 publications
2
14
0
6
Order By: Relevance
“…As Fine and Schiller reported that serial biopsy helps in establishing a histopathological diagnosis in 15% of patients with diarrhoea lasting over four weeks [13]. Also, Kagueyama reported that patients with diarrhoea lasting 15-30 days displayed a high incidence of hitological changes [10].…”
Section: Discussionmentioning
confidence: 99%
“…As Fine and Schiller reported that serial biopsy helps in establishing a histopathological diagnosis in 15% of patients with diarrhoea lasting over four weeks [13]. Also, Kagueyama reported that patients with diarrhoea lasting 15-30 days displayed a high incidence of hitological changes [10].…”
Section: Discussionmentioning
confidence: 99%
“…This statement was also confirmed in this study. Other authors argue that conventional scalpel produces leakage of blood and lymph causing greater swelling and scarring 11,[17][18][19] .…”
Section: ■ Discussionmentioning
confidence: 99%
“…Following the schedule, weeuthanized them by intraperitoneal injection of anesthetics at twice the usual anestheticdose. Once the death was confirmed, we analyzed the abdominal wall to check for complications such as hematoma, infection, suture dehiscence and adhesions 12,13 . Afterwards, we made the skin and subcutaneous incision in the cranial-caudal direction, with resection of the entire ventral wall in 8x6 cm, encompassing the entire incision.…”
Section: Methodsmentioning
confidence: 99%